Transfer Pricing Sebagai Salah Satu Strategi Perencanaan Pajak Bagi Perusahaan Multi Nasional - Paulina Permatasari (Bina Ekonomi, 2004)
Transfer pricing is a classical issue in international transaction. From government view, transfer pricing can reduce potential government income especially from tax sector because multinational enterprise tend to shift their tax obligation from high tax countries to low tax countries. From corporate view, companies are trying to reduce their cost and their corporate income tax. For multinational corporate, transfer pricing is one of effective strategies to compete with their competitors.